THE LIFE TABLE OF Spodoptera pectinicornis Hampson AS BIOLOGICAL CONTROL AGENT OF WATER LETTUCE (Pistia stratiotes L.) WEED - Lyswiana Aphrodyanti; Abdul Haris; Lidia Luisa Momongan (TROPICAL WETLAND JOURNAL, 2017)
The table of life can provide information on birth (natality), death (mortality) and the opportunity to breed, so it can be used as a parameter of the behavior of population development.The purpose of this study was to determine the calculation of life table of S. pectinicornis Hampson as biological control agent of water lettuce (P. stratiotes) weed.The table of life is done by observing survival ability, mortality and fecundity of S. pectinicornis of a cohort of 300 eggs by looking at all the stages from egg, larva, pupa, and imago, and fecundity of female imago per day. The research was conducted in a condition of unlimited food resources and environment free of natural enemies. Parameters observed were gross reproductive rate (GRR), net reproductive rate (Ro), average of generation time (T), intrinsic rate of growth (r), and limited rate of growth (λ). The research result of the life table calculation showed that GRR value was 350.29, the value of net reproductive rate (Ro) was 19.59 descendants, the average of generation time (T) was 29.47 days, the value of intrinsic rate of accretion (r) was 0.10 and the value of limited rate of accretion (λ) was 1.11.